Pernikahan Dini Dalam Perspektif Hukum Islam - Amalia, Fatma (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
Child marriage has become one of the most controversial issues in Islamic law (fiqh). Some scholars approve the practice without any reservations while others do not. In my opinion, we have to take into account the advantages and disadvantages of child marriage in broader sense before we decide to allow or disallow this to happen. Making a clear legal status of such child marriage is necessary because the substance of the Islamic law is create a better life for society now and in the future. Islamic law should cater the humanitarian vision and be relevant to the changing situation of our dynamic community. If it is found that child marriage in contemporary societies has resulted in many negative effects then it should be legally disapproved.